Sistem High Rate Algae Reactor (HRAR) Untuk Menyisihkan BOD Pada Palm Oil Mill Effluent (POME) - Vonny Meidina Rizani; Shinta Elystia; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
In Indonesia, Palm Oil Mill Effluent (POME) treatment generally used open pond system, but this system cannot utilize nutrients properly. High Rate Algae Reactor (HRAR) system can be the solution of this problem. HRAR can increase the growth of microalgae and bacterial, while eliminating pollutants in wastewater. This research aim to investigate the effect of microalgae suspension concentration towards the removal efficiency of Biochemical Oxygen Demand (BOD). Based on the research results, 25% of microalgae suspension concentration showed the best removal efficiency of BOD, was 86,07%.Keywords: High Rate Algae Reactor (HRAR), Microalgae-Bacterial Consortium, Palm Oil Mill Effluent (POME), Biochemical Oxygen Demand (BOD),